Human rights and poverty reduction in Ghana: A rights based approach - Adagewine, G. (University of Ghana, 2009)
The study examined how legal rules can be used to enforce human rights and constitutional principles in order to facilitate poverty reduction in Ghana. It also examined how human rights and poverty relate and the relevance of that relation to poverty reduction. In addition, the study examined the concepts of human rights and poverty as well as the rights based approach to poverty reduction. It is argued in the study that the objects of human rights are required to reduce poverty. The methodology used in the study was library based. It took the form of a review of relevant literature on poverty, human rights and the rights based approach to poverty reduction. It also took the form of a discussion of relevant provisions of the 1992 Constitution of Ghana and other legislation. The methodology also took the form of a discussion of selected cases decided by the Supreme Court of Ghana. The conclusion from the study is that is a link between poverty and human rights. It has also been established that the legal enforcement of human rights and rights based principles can facilitate poverty reduction. The challenge, however, for the poor is the economic constraints they face that make it difficult for them to utilize avenues that exist for the vindication of their rights. It is therefore suggested that institutions like the Legal Aid Board and the Commission on Human Rights and Administrative Justice should be sufficiently resourced as well as their mandate also ought to be amplified so as to enable them assist the poor and vulnerable in society assert their legal rights under the law.
LLM
Keywords: Human rights; Poverty reduction; Ghana; Humanitarian law